Pengaruh Kepribadian Extraversion terhadap Perilaku Narsisme di Media Sosial Dimoderasi Social Media Engagement pada Usia Dewasa Awal - Alfiah, Haura; Maslihah, Sri (JURNAL PSIKOLOGI INSIGHT, 2022)
This study aims to determine the effect of extraversion personality on narcissistic behavior in social media moderated by social media engagement in early adulthood. This research design used quantitative methods with a total of 390 subjects consisting of social media users in the age range of 18-25 years in Bandung. The instruments used in this research are BFI (Big Five Inventory) which has been adapted by Reza (2017), the instrument of narcissism behavior based on seven aspects of narcissism from Raskin and Terry (1988), social media engagement as measured by Social Media Engagement Questionnaire (Przybylski et al., 2013). The data analysis technique used is Moderated Regression analysis (MRA) using SPSS version 25. This study shows the results of social media engagement as a moderating variable of extraversion personality on narcissistic behavior with a significant value of 0,192. Based on these results, it can be concluded social media engagement does not moderate the effect of extraversion on narcissistic behavior.Keywords: extraversionpersonality, narcissistic, socialmediaengagement.Tujuanpenelitianiniyaknimengetahuipengaruhkepribadianextraversionterhadapperilaku narsisme di media sosial yang dimoderasi social media engagement pada usiadewasa awal. Desain penelitian ini menggunakan metode kuantitatif dengan jumlah subjeksebanyak 390 yang terdiri dari pengguna media sosial pada rentang usia 18 – 25 tahun diKotaBandung.InstrumenyangdigunakandalampenelitianiniyakniBFI(BigFiveInventory) yang telah diadaptasi oleh Reza (2015), instrumen perilaku narsismeberdasarkantujuh aspek narsisme dari Raskin dan Terry (1998),socialmediaengagementdiukurdenganmenggunakaninstrumenSocialMediaEngagementQuestionnaire(Przybylskiet al.,2013). Teknikanalisisdatayangdigunakanyaitu Moderated Regression analysis (MRA) menggunakan program SPSS versi 25. Penelitianinimenunjukkanhasilsocial mediaengagementsebagai variabelmoderatorpengaruhkepribadianextraversionterhadapperilakunarsismedengannilaisignifikansisebesar0,192. Berdasarkanhasil tersebut dapat disimpulkan bahwa social mediaengagementtidakmemoderasipengaruhkepribadianextraversionterhadapperilakunarsismedimedia sosial.Kata kunci: kepribadianextraversion, narsisme,socialmediaengagement.Andreassen, C. S., Pallesen, S., Griffiths, M. D. (2017). The relationship betweenaddictive use of social media, narcissism, and self-esteem: Findings from a largenationalsurvey. AddictiveBehaviors,64, 287-293.Bendau, A., Petzold, M. B., Pyrkosch, L., Mascarell Maricic, L., Betzler, F., Rogoll, J.,Große, J., Ströhle, A., Plag, J. (2021). Associations between COVID-19 relatedmediaconsumptionandsymptomsofanxiety,depressionandCOVID-19related   fear in the general population in Germany. European Archives of Psychiatry andClinicalNeuroscience,271(2),283–291Boursier, V., Gioia, F., Griffiths, M. D. (2020). Selfie-engagement on social media: Pathological narcissism, positive expectation, and body objectification–Which is more influential?. Addictive behaviors reports, 11, 1-10.Brailovskaia, J., Bierhoff, H. W. (2016). Cross-cultural narcissism on Facebook: Relationship between self-presentation, social interaction and the open and covert narcissism on a social networking site in Germany and Russia. Computers in Human Behavior, 55, 251-257.Buffardi, L. E., Campbell, W. K. (2008). Narcissism and social networking websites.Personality and SocialPsychology Bulletin, 34(10), 1303–1314.Buss, D. M., Chiodo, L. M. (1991). Narcissistic acts in everyday life. Journal ofPersonality,59(2),179–215.Casale, S., Banchi, V. (2020). Narcissism and problematic social media use: A systematic literature review. Addictive Behaviors Reports, 11, 1-10.Coyne, S., Padilla-Walker, L., Howard, E. (2013). Emerging in a digital world: Adecade review of media use, effects, and gratifications in emerging adulthood.EmergingAdulthood, 1 (2), 125-137. Depoux, A., Martin, S., Karafillakis, E., Preet, R., Wilder-Smith, A., Larson, H.(2020).ThepandemicofsocialmediapanictravelsfasterthantheCOVID-19 outbreak.Journal of travel medicine,27(3), 1-2.Di Gangi, P. M., Wasko, M. (2016). Social media engagement theory: Exploring theinfluence of user engagement on social media usage. Journal of Organizational andEndUser Computing,28(2), 53–73.Dunas, D. V., Vartanov, S. A. (2020). Emerging digital media culture in Russia: Modeling the media consumption of generation Z. Journal of Multicultural Discourses, 15(2), 186-203.Fitri, R. A., Munandar, A. (2018). The effect of corporate social responsibility, profitability, and leverage toward tax aggressiveness with size of company as moderating variable. Binus Business Review, 9(1), 63-69.Gentile, B., Twenge, J. M., Freeman, E. C., Campbell, W. K. (2012). The effect of social networking websites on positive self-views: An experimental investigation. Computers in human behavior, 28(5), 1929-1933.Grubbs, J. B., James, A. S., Warmke, B., Tosi, J. (2022). Moral grandstanding, narcissism, and self-reported responses to the COVID-19 crisis. Journal of Research in Personality, 97, 1-10.Habibi, M. R., Laroche, M., Richard, M. O. (2014). The roles of brand community and community engagement in building brand trust on social media. Computers in Human Behavior, 37, 152-161.Hetz, P. R., Dawson, C. L., Cullen, T. A. (2015). Social media use and the fear of missing out (FoMO) while studying abroad. Journal of Research on Technology in Education, 47(4), 259-272.Howay, L., Pudjibudojo, J. K., Pandjaitan, L. N. (2019). Hubungan antara big fivepersonality traits dan internal locus of control dengan self-directed learning pada  mahasiswa fakultas kedokteran. Jurnal Kreatif Online,7(2), 79–93.Kircaburun, K., Alhabash, S., Tosuntaş, Ş. B., Griffiths, M. D. (2020). Uses andgratificationsofproblematicsocialmediauseamonguniversitystudents:A simultaneousexaminationofthebigfiveofpersonalitytraits,socialmediaplatforms, and social media use motives. International Journal of Mental HealthandAddiction, 18(3),525–547.Ksinan, A. J., Vazsonyi, A. T. (2016). Narcissism, internet, and social relations: Astudyoftwotales.PersonalityandIndividualDifferences,94,118–123.Liu, Y., Bakici, T. (2019). Enterprise social media usage: The motives and the moderating role of public social media experience. Computers in Human Behavior, 101, 163-172.Mahadevan, N., Jordan, C. (2022). Desperately seeking status: How desires for, andperceived attainment of, status and inclusion relate to grandiose and vulnerablenarcissism.PersonalityandSocialPsychologyBulletin,48(5),704–717.Mahendra, B. (2017). Eksistensi sosial remaja dalam Instagram (sebuah perspektif komunikasi). Jurnal Visi Komunikasi, 16(1), 151-160.Marshall, T. C., Lefringhausen, K., Ferenczi, N. (2015). The big five, self-esteem,and narcissism as predictors of the topics people write about in Facebook statusupdates.PersonalityandIndividualDifferences,85,35–40.McCrae,R.R.(1992).Thefive-factormodelofpersonalityanditsrelevancetopersonality    disorders. Journal of Personality Disorders, 6(4), 343–359.McCrae, R. R., Costa, P. T. (2003). Personality in adulthood: A five-factor theoryperspective.Guilford Press.Muflikhah, S. (2019, April). Management of social media as one of the Arabic language learning media in the millennial era. In International Conference of Moslem Society, 3, 305-316.Neel, R., Kenrick, D., White, A., Neuberg, S. (2015). Individualdifferences infundamental social motives. Journal of Personality and Social Psychology, 110(6), 887-907.Nurjanah, N. (2018). Pemanfaatan media sosial masyarakat sadar wisata dalam mempromosikan potensi wisata baru. Medium, 6(2), 39-50.Paulhus, D. L., Williams, K. M. (2002). The dark triad of personality: Narcissism,machiavellianism and psychopathy. Journal of Research in Personality, 36(6), 556–563.Przybylski,A.,Khap.,Murayama,K.,Dehaan,C.R.,Gladwell,V.(2013).Motivational,emotional,andbehavioralcorrelatesoffearofmissingout. Computers in Human Behavior, 29(4), 1841–1848.Raskin, R. N., Terry, H. (1988). A principal component analysis of the narcissisticpersonality inventory and further evidence of its construct. Journal of PersonalityandSocial Psychology, 54(5), 890-902.Reza, A. M. (2017). Pengaruh tipe kepribadian dan harapan terhadap penyesuaian diri anak didik pemasyarakatan. Jurnal Psikologi Insight, 1(1), 66-81.Saputra, A. (2019). Survei penggunaan media sosial di kalangan mahasiswa kota padang menggunakan teori uses and gratifications. Baca: Jurnal Dokumentasi Dan Informasi, 40(2), 207-216.Syahreza, M. F., Tanjung, I. S. (2018). Motif dan pola penggunaan media sosial Instagram di kalangan mahasiswa Program Studi Pendidikan Ekonomi UNIMED. Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2(1), 61-84.Wang, D. (2017). A study of the relationship between narcissism, extraversion, drive forentertainment, and narcissistic behavior on social networking sites. Computers inHumanBehavior, 66, 138–148. Wigati, D. G., Nurhayati, S. R. (2021). Pengaruh kecemasan komunikasi terhadapintensitas penggunaan media sosial pada individu di usia emerging adulthood.ActaPsychologia, 3(1), 46-51.Xiang.Y.T., Yang. Y., Li. W, Zhang. L., Zhang. Q., Cheung. T., Ng CH. (2020).Timely mental health care for the 2019 novelCoronavirus outbreak is urgentlyneeded.The LancetPsychiatry, 7(3), 228-229.Zywica, J., Danowski, J. (2008). The facesof Facebookers:Investigating socialenhancementandsocialcompensationhypotheses;predictingFacebook™andoffline popularity from sociability and self-esteem, and mapping the meanings ofpopularitywith semantic networks. Journal of Computer-Mediated Communication, 14(1), 1-34.